Improving Community Health through Counseling, Health Screening, and Group Exercise in Daenggune Village, Kinovaro District, Sigi: Peningkatan Kesehatan melalui Penyuluhan, Pemeriksaan, dan Senam Bersama di Desa Daenggune, Kecamatan Kinovaro, Sigi - Wendi Muhammad Fadhli; Ratna Mentari; Fanissa Nur Ramadani D; Nur Rahmah; Faradillah; Anissa Anggraini; Wulan Savitri (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Non-communicable diseases (NCDs) remain a major public health challenge in rural areas due to low health literacy and limited access to healthcare services. This condition was also identified in Daenggune Village, Kinovaro Sub-district, Sigi Regency. This community service program aimed to improve community understanding of NCD prevention and to enhance elementary school students’ knowledge of Clean and Healthy Living Behavior (PHBS) through an integrative approach. The activities were conducted using a pre-experimental one-group pretest–posttest design, encompassing health counseling, practice-based PHBS education, group physical activities, and free health screenings. Knowledge improvement was analyzed using a paired t-test, supported by observations of participant engagement and responses. The results demonstrated increased community knowledge regarding NCDs and improved understanding of PHBS among elementary school students, accompanied by high levels of community participation. These findings indicate that an integrative, community-based approach is effective in strengthening health literacy and awareness in rural communities and may serve as a model for enhancing promotive and preventive health programs at the village level.